The K-transect in west Greenland: Automatic weather station data (1993–2016). Issue 1 (1st January 2018) - Smeets, Paul C. J. P.; Kuipers Munneke, Peter; van As, Dirk; van den Broeke, Michiel R.; Boot, Wim; Oerlemans, Hans; Snellen, Henk; Reijmer, Carleen H.; van de Wal, Roderik S. W.
ABSTRACT: We present twenty-three years (1993–2016) of automatic weather station (AWS) data, collected along the K-transect near Kangerlussuaq in west Greenland. The transect runs from east to west, roughly perpendicular to the ice sheet edge at about 67° N. The K-transect originated from the Greenland Ice Margin Experiments (GIMEX), held in the summers of 1990 and 1991. Until recently, surface mass balance and ice velocity measurements were performed at nine locations along the K-transect, of which four are equipped with AWS: two in the ablation zone at approximately 500 m and 1, 000 m asl, one at the approximate equilibrium-line altitude (~1, 500 m asl), and one in the lower accumulation zone (~1, 850 m asl) at distances of 5, 38, 88, and 140 km from the ice edge, respectively. Here, we present an overview of the various AWS types and their data corrections, quality, and availability, including a preliminary trend analysis. Recent increases in temperature and radiation components are associated with the frequent occurrence of anti-cyclonic conditions in west Greenland, resulting in clear skies and relatively warm summers. Strong melt concurs with a decrease in winter accumulation, lowering the surface albedo of the ice sheet. The AWS situated at 1, 500 m asl, the former equilibrium-line altitude (ELA), observed almost a doubling of the summertime net shortwave radiation since 2004; as a result, the ELA along the K-transect has been steadily increasing and is currently situated well above 1, 700 m asl.